Idiulūjiyyah wasāʼil al-iʽlām al-jamāhīriyyah al-Indūnisiyyah ʽibar al-internet fi naql akhbār aş-şirāʽ as-siyāsī fī asy-syarq al-awsa - Yufni Faisol; Syofyan Hadi; Reflinaldi Reflinaldi (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2021)
This study aims to explore the forms of information reproduction in online mass media, with specific issues on Middle East conflicts. The present study adopts a qualitative descriptive model. The data were collected from the news reports on the Syrian conflicts by some leading online news platforms such as Republika, Kompas and Tempo. The data were taken from January to October 2018 and were analyzed using the qualitative analysis stages of the Miles and Huberman model. The research findings indicate that each mass media has differences in reproducing Middle East conflict information, in terms of their data source and point of view of news reporting. Republika tends to take the opposition's point of view to the Syrian government so that it puts the United States and its allies as its main subject. On the contrary, Kompas departed from the point of view of sympathy for the Syrian government and its allies, jeopardizing the United States and its allies in reporting. The third media, Tempo, takes the point of view of narrating events chronologically and focuses a lot on humanitarian issues in the news they deliver.